Penerapan Etika Komunikasi Interpersonal Pada Mahasiswa Program Diploma IPB - Enden Darjatul Ulya; Amiruddin Saleh; Wahyu Budi Priatna (Jurnal Komunikasi Pembangunan, 2016)
This study aimed to answer few questions regarding the research namely 1) to analyse the application of interpersonal communication ethics in students of Diploma Program at Bogor Agricultural University (IPB); 2) to analyse the relationship between the application of communication ethics with individual characteristics of Diploma Program students at Bogor Agricultual University; 3) to analyse the relationship between the application of interpersonal communication ethics with family characteristics of Diploma Program students at Bogor Agricultural University. The study was designed as an explanatory research to look for relationships or correlational; 4) to analyse the relationship between the level of knowledge and communication ethics information source. The research site was selected purposively, which is the Diploma Program Campus of Bogor Agricultural University with sample size of 197. Results showed that respondent individual characteristics were mostly female, from mixed ethnicity and Muslim. The sample was from 14 vocational programs in the Diploma Program of Bogor Agricultural University and currently studying in the third semester. The majority of the sample originated from urban areas, had mid-range allowance and a few were active in organisations. The family characteristics of respondents were from intact family with the parents having high level of education, the majority of fathers worked as entrepreneurs and the majority of mothers were stay-at-home mothers. The respondents had high level of family income. The respondents had low level of communication ethics knowledge and information sources about communication ethics were mostly from family. The application of respondents’ communication ethics was adequate. Through correlational analysis using Chi-square it is obtained that the application of communication ethics is correlated with the characteristics of respondents in the variable respondents’ residence of origin. Meanwhile, there is no correlation between communication ethics of respondents with the variable family characteristics, and no correlation between respondents’ communication ethics with the level of knowledge and communication ethics information source.Keywords: communication ethics, individual characteristics, family characteristics, knowledge and information source, interpersonal communication